Fragility analysis of high-rise modular buildings with uncertain modal properties equipped with multiple vertically distributed tuned liquid dampers - Hickey, John; Moore, Hollie; Broderick, Brian; Fitzgerald, Breiffni (My University, 2026)
Application of modular construction techniques in high-rise structures is becoming increasingly popular. This innovative form of construction is relatively novel, with limited in-situ studies of modular buildings leading to uncertainty surrounding the inherent dynamic properties such as natural frequency and damping ratio. This results in difficulty predicting the dynamic response of high-rise modular buildings reliably and ensuring service ability limit requirements are satisfied. For any lightweight and flexible high-rise building, serviceability limits can become a governing design criterion. Given the novelty of the construction methodology, there is substantial uncertainty over the modal properties, with outstanding questions about how to effectively predict natural frequency and the inherent level of damping. When uncertainty surrounds the modal properties of a structure, and hence the dynamic response, auxiliary damping can aid in controlling accelerations and ensuring habitability requirements are satisfied. This paper simulates the dynamic response of one of Europe’s tallest modular buildings, Ten Degrees, located in London, United Kingdom, with the aim of understanding the potential benefits of auxiliary damping in the presence of uncertainty. Both irreducible aleatory uncertainty arising from stochastic wind excitation and initial and reduced epistemic uncertainty in modal properties before and after in-situ monitoring are considered. Multiple Vertically Distributed Tuned Liquid Dampers (MVDTLDs) are employed in the model to assess the improvement in reliability of the structure adhering to ISO 10,137 peak acceleration limits for occupant comfort. Fragility curves are calculated to demonstrate the effectiveness of MVDTLDs in reducing the dynamic response and ensuring occupant comfort despite uncertainty in inherent dynamic properties. MVDTLDs are shown to be an effective control measure, performing more effectively than a single TLD at roof level and improving the reliability of high-rise modular buildings in satisfying habitability requirements.
PUBLISHED
Keywords: Modular construction; Wind-induced acceleration; Reduced-order modelling; Multiple vertically distributed tuned liquid dampers; Fragility analysis; Smart & Sustainable Planet; Structural Dynamics; Structural Engineering; Vibration and Accoustic Engineering; Wind, Wind Energy Engineering